CroDeriV: a New Resource for Processing Croatian Morphology - Šojat, Krešimir (Array, 2014)
The paper deals with the processing of Croatian morphology and presents CroDeriV ― a newly developed language resource that contains data about morphological structure and derivational relatedness of verbs in Croatian. In its present shape, CroDeriV contains 14 192 Croatian verbs. Verbs in CroDeriV are analyzed for morphemes and segmented into lexical, derivational and inflectional morphemes. The structure of CroDeriV enables the detection of verbal derivational families in Croatian as well as the distribution and frequency of particular affixes and lexical morphemes. Derivational families consist of a verbal base form and all prefixed or suffixed derivatives detected in available machine readable Croatian dictionaries and corpora. Language data structured in this way was further used for the expansion of other language resources for Croatian, such as Croatian WordNet and the Croatian Morphological Lexicon. Matching the data from CroDeriV on one side and Croatian WordNet and the Croatian Morphological Lexicon on the other resulted in significant enrichment of Croatian WordNet and enlargement of the Croatian Morphological Lexicon.